Molecular mechanism of tumour necrosis factor alpha regulates hypocretin (orexin) expression, sleep and behaviour. Issue 10 (6th August 2019) - Zhan, Shuqin; Che, Pulin; Zhao, Xue‐ke; Li, Ning; Ding, Yan; Liu, Jianghong; Li, Spring; Ding, Karyn; Han, Lynn; Huang, Zhaoyang; Wu, Liyong; Wang, Yuping; et al.
Abstract: Hypocretin 1 and hypocretin 2 (orexin A and B) regulate sleep, wakefulness and emotion. Tumour necrosis factor alpha (TNF‐α) is an important neuroinflammation mediator. Here, we examined the effects of TNF‐α treatment on hypocretin expression in vivo and behaviour in mice. TNF‐α decreased hypocretin 1 and hypocretin 2 expression in a dose‐dependent manner in cultured hypothalamic neurons. TNF‐α decreased mRNA stability of prepro‐hypocretin, the single precursor of hypocretin 1 and hypocretin 2. Mice challenged with TNF‐α demonstrated decreased expression of prepro‐hypocretin, hypocretin 1 and hypocretin 2 in hypothalamus. In response to TNF‐α, prepro‐hypocretin mRNA decay was increased in hypothalamus. TNF‐α neutralizing antibody restored the expression of prepro‐hypocretin, hypocretin 1 and hypocretin 2 in vivo in TNF‐α challenged mice, supporting hypocretin system can be impaired by increased TNF‐α through decreasing hypocretin expression. Repeated TNF‐α challenge induced muscle activity during rapid eye movement sleep and sleep fragmentation, but decreased learning, cognition and memory in mice. TNF‐α neutralizing antibody blocked the effects of TNF‐α; in contrast, hypocretin receptor antagonist enhanced the effects of TNF‐α. The data support that TNF‐α is involved in the regulation of hypocretin expression, sleep and cognition. The findings shed some lights on the role of neuroinflammation in neurodegenerative diseases including Alzheimer's disease and Parkinson's disease.